2017
DOI: 10.1080/1028415x.2017.1327200
|View full text |Cite
|
Sign up to set email alerts
|

A review on therapeutic potentials of Trigonella foenum graecum (fenugreek) and its chemical constituents in neurological disorders: Complementary roles to its hypolipidemic, hypoglycemic, and antioxidant potential

Abstract: Large populations are the sufferers of the neurological disorders, pointing the need for investigation of such therapeutic interventions which target and delay the underlying pathological hallmarks and exert positive influence on different neurological health problems. Hypolipidemic, hypoglycemic, antioxidant, and immunomodulatory effects of fenugreek and its constituents with their potential role in various neurological disorders were already reported. In future, it would be of even greater interest to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 45 publications
0
30
0
2
Order By: Relevance
“…The extract exerted a significant (P < 0.05) hypoglycaemic effect in normal rabbits which was however short-lived. The hypoglycaemic effect was not significant (P > 0.1) in alloxan-treated rabbits [150] Fenugreek is an excellent source of neutral detergent fiber, proteins, vitamins as well as chemical constituents [172][173][174][175][176]. Hypoglycaemic activity of alcoholic extract of seeds of Trigonella foenum-graecum was tested in both normal and alloxan-induced diabetic rats.…”
Section: Pharmacological and Toxicological Studiesmentioning
confidence: 99%
“…The extract exerted a significant (P < 0.05) hypoglycaemic effect in normal rabbits which was however short-lived. The hypoglycaemic effect was not significant (P > 0.1) in alloxan-treated rabbits [150] Fenugreek is an excellent source of neutral detergent fiber, proteins, vitamins as well as chemical constituents [172][173][174][175][176]. Hypoglycaemic activity of alcoholic extract of seeds of Trigonella foenum-graecum was tested in both normal and alloxan-induced diabetic rats.…”
Section: Pharmacological and Toxicological Studiesmentioning
confidence: 99%
“…Epidemiological studies have shown that people with Obesity and T2DM who received a chronic treatment with antioxidants or anti‐inflammatories, besides showing a greater sensitivity to insulin and low glucose levels, are also at low risk for developing cognitive damage or AD (Walker & Harrison, ). Furthermore, in animal models with hyperglycemia, there are benefits in glucose metabolism at the peripheral level, a decrease in hyperphosphorylation of the tau protein, reduction in the death of neurons, and an improvement in the processes of learning and memory (Lu et al, ; Zameer, Najmi, Vohora, & Akhtar, ). This clearly demonstrates the neuroprotective power of these anti‐inflammatory and anti‐inflammatory agents.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…To our knowledge, no dietary pattern similar to Traditional-Indian-Confinement pattern has been examined in relation to PPD in previous literature for direct comparison. However, key food groups of Traditional-Indian-Confinement diet, such as Indian herbs and seed herbs (e.g., saffron [ 48 , 49 ], fenugreek [ 50 ]), as well as curcumin [ 51 , 52 ] present in curry dishes have previously been reported to be effective in alleviating depressive symptoms via their anti-inflammatory [ 49 , 53 ], neuroprotective [ 54 ], serotonergic [ 55 , 56 ], and hypothalamic pituitary adrenal (HPA) regulation effects [ 57 ]. The Traditional-Indian-Confinement diet also comprises of legumes and pulses and ethnic bread (e.g., chapatti, thosai, idli, and naan), which are rich in B-group vitamins, are crucial for the synthesis of monoamine neurotransmitters and may have helped to establish protection against PPD symptoms [ 20 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%